2022
DOI: 10.3389/fpsyg.2022.951103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of internet usage on consumer impulsive buying behavior of agriculture products: Moderating role of personality traits and emotional intelligence

Abstract: E-commerce has led to a significant increase in internet purchases. The marketing sector is very competitive these days, and marketers have a difficult task: understanding the behavior of their customers. Strategic marketing planning relies heavily on consumer behavior since the consumer acts as the user, buyer, and payer in that process. Consumers’ behavior changes in response to shifts in the factors that influence it. The purpose of this research is to show how Internet usage influence on consumer impulsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
4
22
0
1
Order By: Relevance
“…In this case, consumer haters use different tactics to regulate their emotions such as suppression, reappraisal towards objects like a brand. This concurs with Jie et al (2022), people with high emotional intelligence are not governed solely by their emotions. A fundamental aspect of their emotional intelligence involves comprehending and managing their emotions effectively to arrive at optimal decisions.…”
Section: Brand Haters With High Eisupporting
confidence: 89%
“…In this case, consumer haters use different tactics to regulate their emotions such as suppression, reappraisal towards objects like a brand. This concurs with Jie et al (2022), people with high emotional intelligence are not governed solely by their emotions. A fundamental aspect of their emotional intelligence involves comprehending and managing their emotions effectively to arrive at optimal decisions.…”
Section: Brand Haters With High Eisupporting
confidence: 89%
“…This is in line with this study through error rate: with Self-Control (objective 2.2.4) and with two components of the BFI (objective 3.1.4). Additionally, impulsive behavior was also significantly associated with lower scores of EI and with three components of the BFI: agreeableness, conscientiousness, and extraversion [80], and in this study, it was found that error rate was significantly affected by low scores in two of the BFI components: agreeableness and conscientiousness (objective 3.1.4). Other critical behavior at the workplace is violence, conflict resolution, and organizational citizenship behavior (OCB), where workers do more than just their job description and would promote a good and healthy environment.…”
Section: Discussionsupporting
confidence: 63%
“…They would use social media as a coping mechanism to avoid these negative thoughts (Süral et al, 2019). Lower EI affected people by making them more impulsive, spending more time on social media, and impulsive and negative shopping behavior (Jie, Poulova, Haider, & Sham, 2022). Organizations should take this construct as a trigger to offer more help and support.…”
Section: Discussionmentioning
confidence: 99%